Produktivitas Peralatan Konstruksi Pada Proyek Jaringan Irigasi D.I Baliase Kanan 2 (Paket IV) Kabupaten Luwu Utara - Daktorian Geseng Pongtimbang; Junus Mara; Ari Kusuma (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
The use of construction equipment is very influential on the work in the world of civil engineering, in this case especially heavy equipment. As an effort to increase agricultural production in South Sulawesi province, the Ministry of Public Works and Public Housing (PUPR) further expanded the irrigation network whose source came from the baliase dam in North Luwu Regency. In the construction of this irrigation network, the work process is still at the stage of scattering and compacting the soil using 4 tools, namely Excavator, Dump Truck, Dozzer, and Vibrator Roller. This research is carried out by quantitative methods by way of direct observation on the ground. Data processing is done to find out the productivity of each tool and see if the equipment used in the soil scattering and compaction work is in sync. Based on the results of the study, excavator productivity was 631,299 m3 / hour, DumpTruck was 335.69 m3 / hour, Dozer 603,405 m3 / hour, and Vibrator Roller 4987.5511 m3 / hour. From the results it can be seen that the productivity on the equipment used is out of sync which results in idle time on some tools, therefore the calculation of tool synchronization is carried out. From the results of calculations obtained that there is an addition of tools on dump trucks as many as 10 units to reduce idle time on construction equipment.